PENGARUH KEPEMIMPINAN DAN KOMPENSASI TERHADAP PRESTASI KERJA KARYAWAN PT. PELINDO III CABANG SEMARANG - Dewi, Ema Ratna; Hadi, Sudharto P; Suryoko, Sri (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2014)
The success of a company in carrying out its operations, is inseparable from the quality management of its human resources. One important goal in the management of human resources within an organization is the creation of employee performance . PT. Pelindo III in branch Semarang is a company SOE (State Owned Enterprises) which is rapidly growing in the field of transportation services with the business of loading and unloading containers and shipping (export) and revenue (import) of goods in large quantities. The problem in this study is the decline in the performance of employees. This study aims to determine the effect of leadership (X1) and compensation (X2) on employee performance (Y) PT. Pelindo III in branch Semarang. This type of research is explanatory research. Based on the analysis data can be concluded that there is a leadership influence on job performance and compensation PT. Pelindo III in branch Semarang. The higher or better leadership and compensation received, then the employee performance will increase. Advice can be given in this study is that the leader is always willing to assist employees in dealing with the difficulties of working so that the employee's job easier and lighter and more quickly resolved to the next job. In addition, need to reconsider the granting overtime pay in accordance with the given task, considering the employees have to work after hours. Meanwhile, for the quality of works are expected the employee to work more carefully and not rush in carrying out the tasks assigned, if necessary, re-inspection and supervision of the work is done to avoid mistakes in the work so that the quality of work can be maintained and increased as expected the company.